2021
DOI: 10.15835/nsb13210936
|View full text |Cite
|
Sign up to set email alerts
|

Morphological, physiological, and biochemical responses to NaCl-induced salt stress in mungbean (Vigna radiata L.) varieties

Abstract: Seventeen mungbean varieties [Vigna radiata (L.) R. Wilczek] were subjected to 100-400 mM salinity stress at the germination stage, and the indices of seed germination and early seedling growth were analysed. With the increasing salinity, seed germination and seedling growth attributes were affected in all varieties. Principal component analysis and hierarchical cluster analysis of varietal responses on the germination and seeding growth attributes at 400 mM NaCl separated seventeen varieties into four distinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Although a few studies have reported the effects of NaCl treatment on the total phenol and flavonoid contents in mungbean sprouts, the changes in the contents of individual phytochemicals along with transcriptomic changes remain unexplored ( Koodkaew, 2019 ; Mankar et al., 2021 ). We conducted UHPLC analysis using 14 phenylpropanoid compounds in different groups (flavonoids and phenolic acid), which have been reported to be responsible for antioxidant activity in mungbean seeds and sprouts ( Kim et al., 2009b ; Guo et al., 2012 ; Gan et al., 2016 ; Singh et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although a few studies have reported the effects of NaCl treatment on the total phenol and flavonoid contents in mungbean sprouts, the changes in the contents of individual phytochemicals along with transcriptomic changes remain unexplored ( Koodkaew, 2019 ; Mankar et al., 2021 ). We conducted UHPLC analysis using 14 phenylpropanoid compounds in different groups (flavonoids and phenolic acid), which have been reported to be responsible for antioxidant activity in mungbean seeds and sprouts ( Kim et al., 2009b ; Guo et al., 2012 ; Gan et al., 2016 ; Singh et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%